Value-oriented stakeholder influence on infrastructure projects. Issue 5 (July 2019) - Vuorinen, Lauri; Martinsuo, Miia
Abstract: Project stakeholder management deals with managing and fulfilling stakeholder expectations and has tended to focus on the viewpoint of the focal firm or the project rather than that of the project stakeholders. The stakeholders' perspective is important because they can significantly influence projects, particularly infrastructure delivery involving both public and private actors. This study focuses on the ways that stakeholders pursue influence on projects through their expectation of project value. The goal is to identify the value-oriented reasons for stakeholders to utilize specific influence strategies. A multiple case study was implemented in three transport infrastructure projects. The study argues that stakeholders' expectations of project value creation explain the stakeholder influence strategies utilized. The findings link project value with stakeholder influence strategies and reveal four influence strategies in transport infrastructure projects, differentiated according to their different value priorities. The unique value-influence combinations of public infrastructure projects are revealed and discussed. Highlights: Stakeholders utilize different influence strategies in infrastructure projects Expectations for project value explain the utilized influence strategies Influence strategies include communication, complaints, rules and authority Project value includes environmental and social, financial and systemic value